Peranan Good Corporate Governance Dalam Meminimalisir Praktik Penghindaran Pajak Pada Perusahaan Go Publik - Andrew Gunawan (Politeknik Ganesha Medan, 2022)
The principle of responsibility is one of the important points in the sustainability of a company. Unfortunately, this principle is often ignored, one of which is the prevalence of tax avoidance practices. Tax avoidance is not something